THE INFLUENCE OF FINANCIAL TECHNOLOGY (FINTECH), FINANCIAL LITERACY, AND INCOME LEVEL ON INVESTMENT DECISIONS OF THE MILLENNIAL GENERATION IN SIDOARJO - Arie Christian Fidelio; Is Fadhilah (Suluh Adiluhung Publisher (SAPub), 2025)
Technological developments in the digital era have transformed various aspects of life, including the financial sector, where Financial Technology (FinTech) has emerged as an innovative solution that facilitates access to investment for the public, especially millennials. This study analyzed the influence of Financial Technology (FinTech) usage, Financial Literacy, and Income Level on the Investment Decisions of the millennial generation in Sidoarjo. The method used a quantitative approach with multiple linear regression analysis techniques. Data was collected through questionnaires distributed to millennials investing in various financial instruments. The results showed that Financial Technology (FinTech) usage and Financial Literacy had a significant influence on Investment Decisions, while income level had moderate influence. These findings provided insights into Financial Technology (FinTech) developers, financial institutions, and investors in understanding the factors that influence the Investment Decisions of the millennials. In conclusion, the increasing usage of technology in financial services, understanding Financial Literacy had been becoming increasingly important to encourage wiser Investment Decisions in the digital era.